Green Supply Chain Management (GSCM) Practices in Malaysian SMEs: A Comparative Perspective - Rasit , Zarinah Abdul; Zakaria , Maisurah; Hashim , Marshita; Ramli , Aliza; Mohamed, Muzrifah (International Journal of Psychosocial Rehabilitation, 2020)
Environmental issues associated to rising pollution have prompted many organisations to incorporate the green supply chain management (GSCM) in producing and delivering products to their customers. Nevertheless, the implementations of GSCM practices among Malaysian Small and Medium Enterprises (SMEs) is still scarce, yet SMEs are the main contributors to the nation’s economy. Consequently, the ISO 14001 certified SMEs from the manufacturing sector were selected for this study which aims to examine the relationship between GSCM practices such as eco-design, green purchasing, environmental cooperation, and reverse logistics with sustainability performance. Using the resourced based theory, this study examined the extent of GSCM practices, both extensive and less extensive GSCM practices and sustainability performance. The data was collected through an online survey questionnaire which was distributed to the respective SMEs in the manufacturing sector through email and analysed using the regression analysis. The results reveal that firms with extensive GSCM practices and less extensive GSCM practices have a strong positive relationship with sustainability performance. Only two dimensions of GSCM practices which are eco-design and environmental cooperation have significantly contributed to sustainability performance. The lack of green purchasing practices was identified among SMEs and the implementation of this practice should be encouraged. The results of this study indicate that GSCM practices are very important for organisations particularly SMEs to achieve business sustainability.